2017
DOI: 10.1080/13557858.2017.1346187
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and obesity: is there a difference in association between the Asian- and African- Surinamese adult population?

Abstract: Meeting PA recommendations, particularly within the commuting and leisure time domains, is associated with lower obesity prevalence in the total population. Among the African-Surinamese population, PA within the leisure time domain, more active minutes/week and higher levels of total volume are associated with a lower obesity prevalence. This is not found in the Asian-Surinamese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…21 CVD is the major cause of death (28%) and several studies on CVD risk factors prevalence in Suriname, have shown a high and rising prevalence of these risk factors. 22 , 23 , 24 , 25 , 26 , 27 The Suriname Health Study, for instance, demonstrated a prevalence of 26% for HT, 14% for DM and approximately 30% of people between 55 and 64 years of age with three or more CVD risk factors. 28 , 29 This high prevalence of risk factors may result in a high CVD and HF burden.…”
Section: Introductionmentioning
confidence: 99%
“…21 CVD is the major cause of death (28%) and several studies on CVD risk factors prevalence in Suriname, have shown a high and rising prevalence of these risk factors. 22 , 23 , 24 , 25 , 26 , 27 The Suriname Health Study, for instance, demonstrated a prevalence of 26% for HT, 14% for DM and approximately 30% of people between 55 and 64 years of age with three or more CVD risk factors. 28 , 29 This high prevalence of risk factors may result in a high CVD and HF burden.…”
Section: Introductionmentioning
confidence: 99%
“…These data from 1973 might aid in the understanding of the high cardiovascular risk burden recently reported in the randomly selected urban citizens participating in the Healthy Life in Suriname (HeliSur) study [1, 2]. In this study in the population of Paramaribo (N = 250.000 citizens, with a national population of 560.000), a random sample (n = 1800) of citizens aged 18–70 years was drawn in 2013 (n = 1157 included, mean age 42 years; 37% men; 40% of African ancestry and 43% of South Asian ancestry) [1, 2].…”
Section: Objectivementioning
confidence: 99%
“…In this study in the population of Paramaribo (N = 250.000 citizens, with a national population of 560.000), a random sample (n = 1800) of citizens aged 18–70 years was drawn in 2013 (n = 1157 included, mean age 42 years; 37% men; 40% of African ancestry and 43% of South Asian ancestry) [1, 2]. …”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there is only one other study that has examined the determinants of any weight problem in Suriname. More specifically, data from the Healthy Life in Suriname (HELISUR) study shows that the obesity prevalence ratio was significantly lower in participants meeting the WHO physical activity recommendations, in particular those regarding commuting and leisure time domains [ 19 ]. The authors discovered that active minutes/week and total volume of activity were negatively associated with obesity for all adults in the African-Surinamese members but not in the Asian-Surinamese population.…”
Section: Introductionmentioning
confidence: 99%